Dual roles of innate immune cells and cytokines in shaping the breast cancer microenvironment - Zhang, Chen; Liu, Wei; Yang, Ping; Lin, Rubing; Pu, Lulan; Zhang, Hongying (Frontiers in Immunology, 2025)
Breast cancer remains the most frequently diagnosed malignancy and a leading cause of cancer-related mortality among women worldwide. Increasing evidence underscores the pivotal yet paradoxical roles of innate immune cells and their associated cytokines in orchestrating the dynamic landscape of the breast tumor immune microenvironment (TIME). Innate immune effectors, including tumor-associated macrophages (TAMs) and natural killer (NK) cells, exert dual functions by either initiating robust antitumor responses or facilitating immune evasion, metastatic dissemination, and therapeutic resistance. For instance, MDSCs suppress T and NK cell activity via STAT3/NF-κB signaling and modulate the cytokine milieu through IL-10 and TGF-β. Similarly, M2-polarized TAMs promote angiogenesis, epithelial–mesenchymal transition, and chemoresistance via IL-10/STAT3/Bcl-2 pathways. In contrast, NK cells and CD103+ DCs mediate tumor cell cytolysis and prime antigen-specific immunity, though their activity is frequently compromised in advanced disease. Moreover, key cytokines and chemokines, including IL-6, IL-10, IL-8, TNF-α, TGF-β, and CCL2/5, demonstrate subtype-specific and context-dependent effects, acting as both tumor-promoting and tumor-suppressing agents through complex signaling networks. This review highlights the dualistic nature of innate immune components in breast cancer, discusses their prognostic and therapeutic implications, and proposes novel intervention strategies, such as TAM repolarization, and cytokine modulation, to reprogram the TIME and restore effective immune surveillance, particularly in aggressive subtypes like triple-negative breast cancer.